The Effect of Trier Social Stress Test (TSST) on Item and Associative Recognition of Words and Pictures in Healthy Participants - Guez, Jonathan; Saar-Ashkenazy, Rotem; Keha, Eldad; Tiferet-Dweck, Chen (Frontiers in Psychology, 2016)
Psychological stress, induced by the Trier Social Stress Test (TSST), has repeatedly been shown to alter memory performance. Although factors influencing memory performance such as stimulus nature (verbal /pictorial) and emotional valence have been extensively studied, results whether stress impairs or improves memory are still inconsistent. This study aimed at exploring the effect of TSST on item versus associative memory for neutral, verbal, and pictorial stimuli. 48 healthy subjects were recruited, 24 participants were randomly assigned to the TSST group and the remaining 24 participants were assigned to the control group. Stress reactivity was measured by psychological (subjective state anxiety ratings) and physiological (Galvanic skin response recording) measurements. Subjects performed an item-association memory task for both stimulus types (words, pictures) simultaneously, before, and after the stress/non-stress manipulation. The results showed that memory recognition for pictorial stimuli was higher than for verbal stimuli. Memory for both words and pictures was impaired following TSST; while the source for this impairment was specific to associative recognition in pictures, a more general deficit was observed for verbal material, as expressed in decreased recognition for both items and associations following TSST. Response latency analysis indicated that the TSST manipulation decreased response time but at the cost of memory accuracy. We conclude that stress does not uniformly affect memory; rather it interacts with the task’s cognitive load and stimulus type. Applying the current study results to patients diagnosed with disorders associated with traumatic stress, our findings in healthy subjects under acute stress provide further support for our assertion that patients’ impaired memory originates in poor recollection processing following depletion of attentional resources.